Making sense of the international system the promises and pitfalls of contemporary marxist theories of international relations - Lacher, Hannes (Taylor and Francis, 2016)
This chapter focuses on the conceptual and theoretical innovations which have been made, over the last decade, by Marxists in their attempts to come to terms with the international system. It discusses the work of Mark Rupert, Justin Rosenberg and Peter Burnham though others have contributed significantly to this emerging perspective. The chapter sketches out an alternative interpretation of international relations in the capitalist epoch. It suggests that the interstateness of capitalist political space cannot be explained by reference to the nature of capitalism or the 'laws' or 'logic' of capital. Taking the international character of global capitalism to be a contingent aspect of capitalism raises the question of how to theorize capitalism as a totality. This chapter argues that not all social forms of really existing capitalism are necessarily or in all respects the emanations of the capital relation, as the Lukácsian concept of 'expressive totality' suggests. é 2002 Mark Rupcrt and Hazel Smith for selection and editorial matter; individual contributors their contribution.